Vegetables. We set up partnerships and took action to become more competitive - López Fonseca, Ernesto Antonio; Membreño Galeano, Roger Manuel; Gutiérrez Gutiérrez, Jaime Ramón; Lanuza Morán, Wesbter Isaac; Villarreyn, Keyvin Josué; Picado Vanegas, Armando; Cajina González, Nilo Rafael (Catholic Relief Services, 2012)
This publication is the result of a participatory experience capitalization, facilitated by the International Center for Tropical Agriculture for the project “Alliance to Create Opportunities for Rural Development through Agro-enterprise Relationships” (ACORDAR). In this document we systematically recount the experiences generated by ACORDAR Project contributions to strengthening the Vegetable Value Chain through the establishment of partnerships, technology adoption and market access, which took place during the two stages of the project.